(untitled) - Wilken, Peter (Grand Rapids, 1991)
This book introduce about Windows application basics, text output, dialog boxes, displaying graphics, colors and bitmaps. The address book application...
Keywords: Microsoft Windows (tệp máy tính),Microsoft Windows (Computer file)